Real-life experience of chronic hepatitis C treatment in Switzerland: a retrospective analysis (Swiss Medical Weekly, 2024)
BACKGROUND AND AIM: Direct-acting antivirals (DAAs) have revolutionised the management of chronic hepatitis C. We analysed the use of different generations of DAAs over time in Switzerland and investigated factors predictive of treatment failure.METHODS: This retrospective study was conducted within the framework of the Swiss Association for the Study of the Liver and the Swiss Hepatitis C Cohort Study; it included all patients with chronic hepatitis C treated with DAAs between January 2015 and December 2019 at eight Swiss referral centres.RESULTS: A total of 3088 patients were included; 57.3% were male, and the median age was 54 years. Liver cirrhosis was present in 23.9% of the cohort, 87.8% of whom were compensated. The overall sustained virological response (SVR) rate (defined as undetectable HCV RNA at week 12 after the first course of DAA-based treatment) was 96.2%, with an increase over time. The rate of treatment failure dropped from 8.3% in 2015 to 2.5% in 2019. Multivariable analysis revealed that female sex, the use of the latest generation of pangenotypic DAA regimens, Caucasian origin, and genotype (gt) 1 were associated with SVR, whereas the presence of active hepatocellular carcinoma (HCC), gt 3, and increasing liver stiffness were associated with treatment failure. Notably, the presence of active HCC during treatment increased the risk of DAA failure by a factor of almost thirteen.CONCLUSIONS: SVR rates increased over time, and the highest success rates were identified after the introduction of the latest generation of pangenotypic DAA regimens. Active HCC, gt 3 and increasing liver stiffness were associated with DAA failure.